PELATIHAN E-LEARNING DAN PENGEMBANGAN KONTENBERBASIS PERANGKAT LUNAK OPEN SOURCEBAGI GURU-GURU SMK DI KABUPATEN KULONPROGO - Deny Budi Hertanto, Nurhening Yuniarti, Herlambang Sigit Pramono, Didik Hariyanto (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2011)
Training of PPM aims to provide a knowledge of science andtechnology on how to create e-learning and developing e-learning content.The software used as a media creation software is the LMS (LearningManagement System) Moodle based on an open source. While the trainee isa vocational school teachers at Kulonprogo.The process begins with registration of participants with theminimum requirements are able to operate a computer properly. Provisionof material starting from the introduction of internet, website and serverinstallation process as well as installation of Moodle software. After thatprovided the core material on how to set courses, course management anduser management using Moodle. The material is the process of uploadingthe website on the internet. The material concludes with providingindependent tasks for each participant to create and develop their owncustomized e-learning. In the process of making an independent task,participants are given assistance in the form of consultation for those whohave difficulties. Independent task is used as the basis for determiningcompetency achievement.Of the participants with the number of 25 teachers, all of them canattend training from beginning to end. In addition, all teachers can completethe task independently well, that is capable of creating and developing elearningand its contents.